2005
DOI: 10.1080/08820530500232092
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations and Treatment of Syphilis

Abstract: Syphilis is a sexually transmitted, chronic, systemic infection caused by the spirochete Treponema pallidum. If left untreated, the disease progresses through four stages, with the potential to cause significant morbidity to any major organ of the body. Frequent syphilitic ocular manifestations, which can occur at any stage of the disease, include interstitial keratitis, anterior, intermediate, and posterior uveitis, chorioretinitis, retinitis, retinal vasculitis and cranial nerve and optic neuropathies. Diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
157
1
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(171 citation statements)
references
References 23 publications
0
157
1
13
Order By: Relevance
“…Ocular involvement in syphilis is rare and typically occurs with secondary or tertiary syphilis (Gaudio, 2006;Kiss et al, 2005;Klig, 2008). Tamesis and Foster (1990) reported that uveitis was the most common ocular manifestation Med.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular involvement in syphilis is rare and typically occurs with secondary or tertiary syphilis (Gaudio, 2006;Kiss et al, 2005;Klig, 2008). Tamesis and Foster (1990) reported that uveitis was the most common ocular manifestation Med.…”
Section: Discussionmentioning
confidence: 99%
“…Almost any part of the eye may be involved in syphilis, including the sclera, cornea, lens, uveal tract, retina, retinal vasculature, optic nerve, pupillomotor pathways, and cranial nerves [15][16][17].…”
Section: Syphilismentioning
confidence: 99%
“…Neurosyphilis with ocular and otologic manifestations is treated identically, although steroids may be used as an adjunctive therapy. 43,[54][55][56][57] The United States CDC, European syphilis guidelines and Canadian Public Health guidelines recommend penicillin desensitisation for penicillin allergic patients in whom ceftriaxone is not an option. 21,37,38 In patients who have improvement, resolution or stabilisation of neurological symptoms and normalisation of CSF abnormalities, treatment for neurosyphilis is deemed successful.…”
Section: Treatment Of Neurosyphilismentioning
confidence: 99%